Islamic Value In Culture (IVIC) Animation - Ristiyanti Wulandari N; Ani Nur Aeni; Muhammad Faishal Badruzaman; Reza Mahendra (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2022)
Islamic culture is evidence of the history of the development of Islam. Starting from the technology used in the past until now. Islamic culture is also a custom or behavior that is maintained until now which is evidence that Islam is an earlier religion. There are many cultures that have survived until now, Indonesia is one country that has experienced Islamic culture for its spread. Unbeknownst to many people, it turns out that many Islamic cultures have social values ​​that are actually important in this life. Indonesia as a witness who has used Islamic culture as a way to spread Islam in the archipelago has forgotten many of the values ​​of that culture, for example in Eid we have a culture of shaking hands which is a form of friendship using Islamic culture. IVIC is an animation medium where IVIC is used to make people aware of these forgotten cultural values ​​in Indonesia.